ANALISIS SEKTOR BASIS DI KABUPATEN GORONTALO UTARA MENGGUNAKAN LOCATION QUENTIENT ANALYSIS - Fahmi Indrayani; Dwi Cahyani (IISIP YAPIS Biak, 2023)
Regional economic growth can be reflected in changes in Gross Regional Domestic (GRD) growth in a region, GRD values can represent the economic growth of a region. To find out which are the basic and non-basic sectors as a reference in development planning. One analysis that can analyze the division of base and non-base sectors can be used Location Quotient (LQ) analysis, so that economic development planning can be realized in a structured manner based on its sectoral potential based on GRD values. The variable used to calculate the economic base is the GRDP value from 2010 to 2021 in North Gorontalo Regency. Based on the LQ value obtained, in 2021 from 17 business fields in North Gorontalo district, there are four business fields that become the base sector in North Gorontalo district, namely the Mining and Quarrying sector with an LQ value of 1.63, agriculture, forestry, and fisheries with an LQ value of 1.37; the Government Administration, defense & mandatory social security sector with an LQ value of 1.18; and other services sector with an LQ value of 1.09.